Subcutaneous ulcerated nodule refractory to antibacterial treatment - Wan Mahmud, Wan Fatimah Suriyani; Ismail, Rasimah (2021)
Sporotrichosis is infection caused by dimorphic fungus Sporothrix schenckii. It occurs worldwide especially tropical and subtropical zone. It manifests as lymphocutaneous skin, fixed cutaneous or disseminated lesion following exposure to contaminated source like animals, plants, or abiotic components. Here, we present a case of a 75-year-old lady with right foot ulcerative nodule that refractory to antibacterial treatment. This case highlights the importance of early recognition and diagnosis of sporotrichosis which may avoid delay diagnosis and prompt effective therapy.